The Integrated Project-Based Approach to Learning (IPBAL) and the Acquisition of Lifelong Learning Skills in Pupils of Government Bilingual Primary Schools in Mbouda Sub-Division - Tembei, Enjei Joan; Len, Kibinkiri Eric (Journal of Education and Training, 2024)
This study was designed to investigate the relationship between the integrated project-based approach to learning and the acquisition of lifelong learning skills in pupils of Government bilingual nursery and primary schools in the Mbouda sub-division. The study was guided by the cognitive development theory of Jean Piaget and the experiential theory of John Dewey. The study adopted a cross-sectional survey design. The sample population for the study was made up of respondents that were Headteachers, and teachers. The population and sample were selected using the purposive sampling technique. The instruments used were closed-ended questionnaires. Data was collected from a sample of 14 head teachers and 80 teachers. Data were analyzed using descriptive and inferential statistics. The hypotheses of the study were tested using a non-parametric Spearman’s rho test. Findings showed that there was a significant, positive, and relatively strong relationship between the identification of problems and learners' acquisition of lifelong skills (R-value 0.504**). Similarly, findings revealed that there was a significant, positive, and strong relationship between the use of appropriate instructional methodologies and learners' acquisition of lifelong skills (R-value 0.630**). Furthermore, findings showed that there was a significant, positive, and relatively strong relationship between collaboration learning and learners' acquisition of lifelong skills (R-value 0.515**). Findings equally revealed that there is a significant, positive, and strong relationship between the integration of ICT in the teaching-learning process and learners' acquisition of lifelong skills (R-value 0.556**). It was concluded that an integrated project-based approach to learning influences the lifelong learning skills in some government bilingual primary schools in Mbouda Sub Division. Based on the findings: it was recommended that teachers should be given the impunities and facilities that can help them identify pupils’ problems and provide possible solutions. Teachers and the community should work together on appropriate instructional methodologies, integrating ICT into the teaching-learning process so that pupils can acquire lifelong learning skills.